Distribution, pollution, and ecological risks of rare earth elements in soil of the northeastern Qinghai–Tibet Plateau. Issue 7 (3rd October 2019) - Wu, Jun; Lu, Jian; Li, Leiming; Min, Xiuyun; Zhang, Zhenhua; Luo, Yongming
ABSTRACT: Information on rare earth elements (REEs) in soils of the Qinghai–Tibet Plateau is very limited. Therefore, this study performed field sampling to explore the concentrations, contamination degree, and potential ecological risks of REEs in soil of the northeastern Qinghai–Tibet Plateau. Concentrations of total REEs (TREEs) ranged from 95.82 to 544.01 mg/kg with average value of 241.81 mg/kg. Light REEs accounted for 72.3%–84.2% of TREEs, whereas Ce was the dominant element. Four methods were employed to evaluate the pollution of soil REEs. About 45.7% of sampling sites exhibited uncontaminated to moderately contaminated levels based on geoaccumulation index values of TREEs. Over 95.7% of sampling sites exhibited deficiency to minimal enrichment based on enrichment factor values of TREEs. The pollution load index evaluation results illustrated that about 85.7% of sampling sites possessed moderate levels of pollution, more serious than those evaluated by modified degree of contamination method. The potential ecological risk indexes of soil REEs in study area ranged from 11.02 to 40.55, showing low risk levels. This study provided important information on REEs in soils of the northeastern Qinghai–Tibet Plateau for soil pollution prevention and control at the high-elevation areas.